Effect of quorum sensing and quenching molecules on inter-kingdom biofilm formation by Penicillium expansum and bacteria. Issue 8 (13th September 2020) - Afonso, Tiago Barros; Simões, Lúcia Chaves; Lima, Nelson
Abstract: The ecology of a biofilm is a complex function of different factors, including the presence of microbial metabolites excreted by the inhabitants of the biofilm. This study aimed to assess the effect of patulin, and N -(3-oxododecanoyl)-L-homoserine lactone (3-oxo-C12 -HSL) on inter-kingdom biofilm formation between a filamentous fungus and bacteria isolated from drinking water. The filamentous fungus Penicillium expansum and the bacteria Acinetobacter calcoaceticus and Methylobacterium oryzae were used as model species. M. oryzae biofilm formation and development was more susceptible to the presence of the quenching molecules than A. calcoaceticus biofilms. Patulin reduced M. oryzae biofilm growth while 3-oxo-C12 -HSL caused an increase after 48 h. The presence of P. expansum had a detrimental effect on M. oryzae cell numbers, while an advantageous effect was observed with A. calcoaceticus. The overall results reveal that quorum sensing and quenching molecules have a significant effect on inter-kingdom biofilm formation, especially on bacterial numbers.